A gender analysis on the participation and choice of improved and local haricot bean (Phaseolus vulgaris L.) by farmers in Cameroon - Siri, Bella N.; Nchanji, Eileen Bogweh; Tchouamo, Isaac R. (Scientific Research Publishing, Inc., 2020)
Men and women farmer participation and choice of variety could guide breeding and drive the adoption of different haricot bean varieties. Thus, understanding how gender influences participation and choice of bean cultivation and marketing is fundamental. The study sought to analyse how socio-cultural norms determine women and men, participation and choice of variety for cultivation and sale in Cameroon’s West region. A mixed-method was used in collecting data from men and women farmers in six subdivisions in the West region of Cameroon in 2019. Result reveals that women provide most of the labour on haricot bean production than men, who are more involved in selling to national and regional markets. Participation and role were driven by socio-cultural norms of what is expected of men and women in a society where women provide food and men income for household upkeep. Women preferred varieties that were less labour intensive and food taste for household consumption while men went for labour intensive as long as they were market-oriented and high yielding. Thus, breeders should develop varieties that are mostly preferred by women, which meet the market and household demand.